Activating transcription factor 4 (ATF4) modulates post-synaptic development and dendritic spine morphology - Liu, Jin; Pasini, Silvia; Shelanski, Michael L.; Greene, Lloyd A. (Frontiers in Cellular Neuroscience, 2014)
The ubiquitously expressed activating transcription factor 4 (ATF4) has been variably reported to either promote or inhibit neuronal plasticity and memory. However, the potential cellular bases for these and other actions of ATF4 in brain are not well defined. In this report, we focus on ATF4’s role in post-synaptic synapse development and dendritic spine morphology. shRNA-mediated silencing of ATF4 significantly reduces the densities of PSD-95 and GluR1 puncta (presumed markers of excitatory synapses) in long-term cultures of cortical and hippocampal neurons. ATF4 knockdown also decreases the density of mushroom spines and increases formation of abnormally-long dendritic filopodia in such cultures. In vivo knockdown of ATF4 in adult mouse hippocampal neurons also reduces mushroom spine density. In contrast, ATF4 over-expression does not affect the densities of PSD95 puncta or mushrooom spines. Regulation of synaptic puncta and spine densities by ATF4 requires its transcriptional activity and is mediated at least in part by indirectly controlling the stability and expression of the total and active forms of the actin regulatory protein Cdc42. In support of such a mechanism, ATF4 silencing decreases the half-life of Cdc42 in cultured cortical neurons from 31.5 to 18.5 hours while knockdown of Cdc42, like ATF4 knockdown, reduces the densities of mushroom spines and PSD95 puncta. Thus, ATF4 appears to participate in neuronal development and plasticity by regulating the post-synaptic development of synapses and dendritic mushroom spines via a mechanism that includes regulation of Cdc42 levels.